Effects of different sets of rolling foam on agility and jumping power performance among basketball players / Muhammad Amir Nasiruddin Mohamad - Mohamad, Muhammad Amir Nasiruddin (Faculty of Sport Science and Recreation, 2019)
The purpose of this study is to investigate the effects of different sets of rolling foam on agility and jumping power performance among basketball players. A total of twelve subjects (N=12) from UiTM Pahang basketball team were selected through purposive sampling. The study compared the post test of agility and jumping power performance test after applying 1 set of rolling foam for one group and 4 sets of rolling foam for another group. All of the subjects will perform three trials for jumping power performance test and two trials for agility test. Both of the groups will performed the tests immediately after applying the treatment. Illinois Agility Test will be the test for measuring agility performance and the time taken recorded using stopwatch while Sargent Jump Test will be the test for measuring the jumping power performance and the distance height between the jumps recorded by using measuring tape. Paired Sample T-Test will be used for the data testing analysis. For the first hypothesis testing, there is a significant effect of different sets of rolling foam on agility performance which the group with 1 set of rolling foam M=15.85(SD=.2633) while the group with 4 sets of rolling foam M=17.08(SD=.l336). The second hypothesis is there is a significant effect on jumping power performance which the group with 1 set of rolling foam M=61.87(SD=1.96) while the group with 4 sets of rolling foam M=53(SD=1.129). To conclude, this finding suggests that 1 set of rolling foam is better than 4 sets in improving agility and jumping power performance